The impact of dividend policy on shareholder wealth in Malaysian oil and gas industry / Najiha Illyana Kamarudin - Kamarudin, Najiha Illyana (Faculty of Business Management, 2018)
This paper aim is to investigate the impact of dividend policy on shareholder wealth in Malaysian oil and gas industry companies. The study consists of yearly data from 2005 until 2017 often public listed oil and gas companies in Malaysia. Oil and gas industry is one of the main industries in the world. Even though there are many oil and gas public listed companies in Malaysia, this study is only focused on ten public listed companies because there is a lack of data sample provided by each company's annual report. The dependent variable is shareholder wealth. It is measured by market price per share. The independent variable is dividend policy and it is measured by dividend payout ratio, dividend per share, earnings per share and retained earnings per share. By using a quantitative method, it shows that two out of four independent variables affect the dependent variables. Multiple regression results show that the dividend per share and earnings per share is a significant relationship with market price per share. While dividend pay-out ratio and retained earnings per share is not a significant relationship with market price per share.